Canola extracts for the control of Botrytis cinerea in vitro and in post-harvest on strawberries - Cláucia, Cuzzi; Santos, Idalmir; Vilani, Andréia; Sonego, Etiane Tanise; Freddo, Álvaro Rodrigo; Mazaro, Sérgio Miguel (Scientia Agraria Paranaensis, 2017)
This study aimed to evaluate the effect of canola extracts obtained by different methods for extraction (alcohol, macerated, watery without reservation time and infusion), for the control of Botrytis cinerea in vitro and gray mold in post-harvest on strawberries cv. Camarosa. In vitro condition two experiments were conducted, being mycelial growth and conidia germination in a factorial 4 x 5, with factors extraction modes and extracts concentrations (0%, 3%, 6%, 9% and 12%), with four replicates. Post-harvest were tested four types of extracts at a concentration of 16%. The design was completely randomized, with four replicates per treatment, and the portion composed of 10 fruits per replicate. Physichochemical parameters and biochemical analyzes were evaluated. The results showed reduction of mycelial growth and conidia germination, depending on the concentrations, but there were no differences between the types of extracts. The higher efficiency of the extracts occurred at a concentration of 8.31%, the assessment within 96 hours. The alcoholic extracts, maceration and infusion reduced rots caused by B. cinerea in post-harvest strawberries. The extracts acted in changing the acidity of fruits and activity of peroxidases, but showed no effect on total soluble solids (TSS), hardness, weight loss, anthocyanins, flavonoids and the enzyme phenylalanine ammonia liase (PAL). The results of this study showed that the canola extracts has the potential to control B. cinerea in vitro and in post-harvest strawberries.